Geotextiles in landfill closures - Christopher, Barry R. (Geotextiles and geomembranes, 1991)
There are numerous areas of geotextile application in landfill covers, each with a somewhat unique set of requirements and considerations for the proper selection and evaluation of the most appropriate material. This paper provides an overview of geotextile requirements and specific references to available design literature for each of these application areas.